Test anxiety in online exams: scale development and validity - Dikmen, Melih (Springer, 2023)
Considering the increasing use of online tests, this study aims to develop an up-to-date and reliable scale to measure university students' online test anxiety. This study was designed by using mixed research model by combining qualitative and quantitative research methods together. The study consisted of four stages: planning, structuring, quantitative evaluation, reliability and validation. While in the first phase an extensive literature review was conducted, students' opinions were obtained to create an item pool in the second phase. In the third phase, the 29-item scale was administered to 442 university students for factor and reliability analysis. A total of nine items were dropped out from the pool. The Cronbach's alpha value was .98. Exploratory factor analysis revealed that the items loaded on two factors: the psychological and physiological anxiety factor (alpha = .95), the technical anxiety factor (alpha = .89). The two-factor solution accounted for more than 63% of the total variance. The final version of the scale was administered to 387 university students for confirmatory factor analysis in the fourth stage. The results proved that the scale had two factors and the fit indices were at an acceptable level. The reliability analysis was run and Cronbach's alpha values were .94 the whole scale, .93 for the psychological and physiological anxiety factor, and .90 for the technical anxiety factor. According to the result, it was concluded that the Test Anxiety Scale for Online Exams is a reliable and valid measurement tool in determining university students' online test anxiety. Finally, recommendations for future research are provided.
Keywords: Online test anxiety; University students; Measurement development; Online learning